Patient Safety Culture in Norwegian Home Health Care - a study protocol - Silje Tollefsen; Oddvar Førland; Ellen C. Tveter Deilkås; Valborg Baste; Gunnar Tschudi Bondevik (Scandinavian University Press (Universitetsforlaget), 2020)
The Safety Attitudes Questionnaire (SAQ) is a widely used instrument to measure safety attitudes among health care providers. The overall aim of this project is to provide research that contributes to developing better patient safety cultures in Norwegian home health care. First we will develop a tool for measuring patient safety culture in home health care services, by validating the Norwegian translation of the SAQ in the home health care setting. Second, we will study safety attitudes amongst health care employees in home health care - and whether patterns in attitudes are related to professional background, gender, age and workplace. Third, we will investigate the experienced quality of collaboration and communication between employees in home health care - and other parts of the health care services. Last, we will compare findings related to safety attitudes across services in primary health care (home health care, nursing homes, out-of-hours clinics and general practitioner (GP) practices). As part of the overall Safety Culture in Primary Care (SIP) project, this project will follow the same design as previous completed SIP studies in other services of primary care in Norway.